Quran's Explanation for Civilizations Fall - Yaseen Rasheed Al Zeebari (Zanco Journal of Human Sciences, 2025)
The Research contains basic rules for Civilization ' s fall, within Quran ' s point of view, The Research is considered as part of History ' s philosophy The Researcher dependded upon thoughts of Holy Quran Explainers, now and elderly. Sometimes be explains the Verse ( Aya ) _ within the modern life standards , which shows the greatness of Holy Quran The Research included Preface about civilization ; Definition of civilization Aspects of civilization , Reasons of civilization ' s fall in Holy Quran Falsification of Reformers and ignoring thern Mutiny of leaders against thinkets , Injustice in selling ss buying , Loose of good morals , Oppression , usatisfaction luxury changing of facts , Neglecting of mail principles , Guilts Ostering of good people out of land ; Leaving he divine rules, kings tyranny atheism, lechery adornment, arrogance, danism Moreover, this study is considered as an ethic program and a constitution for life on the level of individuals and groups for keeping comfortable living The Research included also tentioning of more than sixty personalities with their death dates in Hijra Vs Christ, The Research depended Upon about seventy rwferences